Factors Affecting The Development of Chengdu Kuanzhai Cultural And Creative Industry Investment Group Co.,Ltd. - Liu, Qiaochen; Tantasanee, Somchai (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
This article employs mixed-method research aiming to determine the factors affecting and improving the development level of Chengdu cultural creative industry in Sichuan Province. The research site is Chengdu Kuanzhai Cultural and Creative Industry Investment Group Co., Ltd. The population is made up of company personnel, a total of 130 people, and the sample size is 100 respondents. Research respondents include company managers and employees at staff level. The research instruments include the questionnaire for the quantitative research method and the interview for the qualitative method. The data analyses comprise of multiple linear regression for quantitative analysis and content analysis for qualitative analysis. The research findings show that creative talents, creativity, technology, intellectual property and culture have significant influences on the development of cultural and creative industries in Chengdu, China.